2014
DOI: 10.1002/smr.1661
|View full text |Cite
|
Sign up to set email alerts
|

Understanding sprint velocity fluctuations for improved project plans with Scrum: a case study

Abstract: Starting from the documentation of high sprint velocity fluctuations in a Scrum project, this paper presents a thorough approach to identify the sources of issues arising in the context of Scrum implementation. Given that Scrum provides guidance on identifying process issues but not their root causes, various approaches are explored. This is of great relevance because Scrum defines project schedules relying heavily on sprint velocity and because it is the most widely used agile methodology. The findings provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Albero Pomar et al proposed 2 techniques for predicting future performance of scrum software teams. The first approach relies on plotting the accrued velocity for all previous sprints to identify the trends (downward or upward) of performance.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Albero Pomar et al proposed 2 techniques for predicting future performance of scrum software teams. The first approach relies on plotting the accrued velocity for all previous sprints to identify the trends (downward or upward) of performance.…”
Section: Related Workmentioning
confidence: 99%
“…They also proposed exploiting a traditional (nonagile) project management metric to gauge the amount of completed work over the planned work. The metric is calculated as the ratio of the total earned points over the total points planned in the sprint planning meeting SchedulePerformanceIndicator=EarnedpointsPlannedpoints100 …”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…velocity fluctuation (VF) is a vital graph that product managers watch during sprint planning and execution because it helps them plan more accurately for future sprints. VF has been studied to identify the sources of issues arising in scrum implementations, and it was found that fluctuations in velocity are caused by the team missing their commitments that, in turn, depend on the unaccounted complexities of different sub-systems [56].…”
Section: Productivitymentioning
confidence: 99%
“…VF is another way to monitor SV, and it represents the SV variance from the average. Monitoring the VF helps analyze the root cause of the team missing their commitment [56] and is calculated as the following:…”
Section: Metrics For Productivitymentioning
confidence: 99%